Sistem Pendukung Keputusan Rekomendasi Game Menggunakan Metode Analitycal Hierarchy Process (AHP) (Studi Kasus di Warung Internet Edelweiss) - Sory, Subhan; Br. Ginting, Novita; Rachmawati, Fitria (Rifa'Institute, 2023)
Warnet Edelweiss (Edelweiss internet cafe) is a type of business that provides services and internet network connections, the main services provided to customers are internet browsing and games. Currently, the game is very liked by several groups ranging from adults, teenagers to children. The phenomenon of this game certainly has positive and negative impacts for its users, especially for children who currently dominate the game world. There needs to be a good and appropriate game selection based on age and gender through the application of a decision support system using the Analytical Hierarchy Process (AHP) method. The purpose of this study is to design and apply the AHP algorithm method to create a decision support system in the selection of game recommendations at the edelweiss internet cafe. The stages in this research start from data collection, analysis, design, implementation and system testing. The decision support system for selecting game recommendations at the edelweiss internet cafe has been successfully designed by utilizing the Object Oriented Programming (OOP) design method and the AHP method has been successfully applied. The results of testing with the black box method concluded that the system is running well and can be used.